Integration of Ahlussunah wal Jamaah An-Nahdliyyah Values in the Curriculum of the Islamic Religious Education Study Program Darussalam Islamic Institute of Martapura - Lusiana Lusiana; Kholili Hasib; Vialinda Siswati; Muhammad Sauqi (Jurnal Pendidikan Terapan, 2026)
This study examines the integration of Ahlussunnah wal Jamaah An-Nahdliyah (Aswaja) values into the Islamic Religious Education (PAI) curriculum at the Darussalam Islamic Institute of Martapura. The research responds to the need for graduates who possess academic competence, religious moderation, and character rooted in local socio-cultural values. A qualitative case study approach was employed. Data were collected through semi-structured interviews, participatory observations, and document analysis involving 10 purposively selected participants, consisting of institutional leaders, lecturers, and student representatives. Data were analyzed using thematic analysis supported by NVivo 12 Plus software. The findings reveal that Aswaja values are integrated through three interconnected dimensions: understanding (knowing), practice (doing), and internalization (being). These dimensions are reflected in the institution’s vision and mission, curriculum structure, learning activities, worship practices, and holistic evaluation processes. The curriculum also incorporates Banjar traditions, such as tahlilan, haul commemorations, and grave pilgrimages, as media for character education. The novelty of this study lies in proposing an integrative curriculum model that links Aswaja values with local cultural traditions to strengthen character formation, religious moderation, and graduate adaptability in contemporary society.